Pengaruh Supervisi Akademik dalam Meningkatkan Kinerja Guru - Novebri Novebri; Nadroh Lubis (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2022)
Abstract: The study aims to analyze the influence of academic supervision on teacher performance at the Adnani Islamic Education Foundation in Panyabungan. This research is a type of quantitative research. The data was collected with research instruments in the form of questionnaires distributed to 59 teachers. Data processing techniques using the help of SPSS 20 applications. Based on the results of the data analysis found R2 = 0.328 with a significance level (ρ) of 0.000. This means that there is an influence of academic supervision on teacher performance at the Adnani Islamic Education Foundation in Panyabungan by 32.8%, where if the implementation of academic supervision is improved, teacher performance will also increase. Academic supervision aims to help teachers improve their professional skills in managing learning. Improving teacher ability through academic supervision is expected to have an impact on improving the quality of learning and teacher performance. Keywords: academic supervision; teacher’s performance; Adnani Islamic Education Foundation Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh supervisi akademik terhadap kinerja guru di Yayasan Pendidikan Islam Adnani Panyabungan. Adapun penelitian ini merupakan jenis penelitian kuantitatif. Data dikumpulkan dengan instrumen penelitian berupa angket yang disebar kepada 59 orang guru. Teknik pengolahan data menggunakan bantuan aplikasi SPSS 20. Berdasarkan hasil analisis data ditemukan R2 = 0,328 dengan taraf signifikansi (ρ) 0,000. Ini berarti adanya pengaruh supervisi akademik terhadap kinerja guru di Yayasan Pendidikan Islam Adnani Panyabungan sebesar 32,8%, dimana apabila pelaksanaan supervisi akademik ditingkatkan maka kinerja guru akan semakin meningkat. Supervisi akademik bertujuan membantu guru meningkatkan kemampuan profesionalnya dalam memanajemen pembelajaran. Peningkatan kemampuan guru melalui supervisi akademik diharapkan berdampak pada peningkatan kualitas pembelajaran dan kinerja guru. Kata kunci:supervisi akademik; kinerja guru; Yayasan Pendidikan Islam Adnani